Addition of lemon before boiling chlorinated tap water: A strategy to control halogenated disinfection byproducts - Liu, Jiaqi (Chemosphere, 2020)
Chlorine disinfection is required to inactivate pathogens in drinking water, but it inevitably generates potentially toxic halogenated disinfection byproducts (halo-DBPs). A previous study has reported that the addition of ascorbate to tap water before boiling could significantly decrease the concentration of overall halo-DBPs in the boiled water. Since the fruit lemon is rich in vitamin C (i.e., ascorbic acid), adding it to tap water followed by heating and boiling in an effort to decrease levels of halo-DBPs was investigated. We examined three approaches that produce lemon water: (i) adding lemon to tap water at room temperature, termed “Lemon”; (ii) adding lemon to boiled tap water (at 100°C) and then cooling to room temperature, termed “Boiling + Lemon”; and (iii) adding lemon to tap water then boiling and cooling to room temperature, termed “Lemon + Boiling”. The concentrations of total and individual halo-DBPs in the resultant water samples were quantified with high-performance liquid chromatography-tandem mass spectrometry and the cytotoxicity of DBP mixtures extracted from the water samples was evaluated in human epithelial colorectal adenocarcinoma Caco-2 cells and hepatoma HepG2 cells. Our results show that the “Lemon + Boiling” approach substantially decreased the concentrations of halo-DBPs and the cytotoxicity of tap water. This strategy could be applied to control halo-DBPs, as well as to lower the adverse health effects of halo-DBPs on humans through tap water ingestion.